SOCIAL COMPARISON SEBAGAI MODERATOR INTENSITAS PENGGUNAAN INSTAGRAM DENGAN SELF-ESTEEM - Rahma, Lili Mira Julia; Setiasih, Setiasih (Jurnal Psikologi, 2024)
Instagram social media is one of the media that is widely used to carry out social comparisons with other Instagram social media users which can then affect self-esteem. This study aims to determine the relationship between the intensity of Instagram use and self-esteem with social comparison moderators in emerging adulthood. Selection of participants using a quota sampling technique. This research involved 288 students at university "X" with an age range of 18-27 years, male and female, and Instagram social media users. The research data was collected using the Rosenberg self-esteem scale questionnaire, Instagram intensity scale, and The Iowa Netherlands Comparison Orientation Measure. The study used a correlational design using multiple regression analysis with a moderator. The findings of this study indicate that the intensity of using Instagram and social comparison simultaneously can affect self-esteem but in a low category. Social comparison has also not been proven to act as a moderator variable.